2018
DOI: 10.1016/j.dld.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A real-world, long-term experience on effectiveness and safety of vedolizumab in adult patients with inflammatory bowel disease: The Cross Pennine study

Abstract: Vedolizumab is an effective therapy for inducing and maintaining remission of IBD, with better results for UC, and with a good safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 49 publications
6
47
1
Order By: Relevance
“…The same results were shown by Kopylov et al with similar rates of response and remission both for CD and UC. Other authors found no difference in CD and UC cohorts after the induction phase, while in one study a higher clinical benefit in patients with UC was seen, with a cumulative clinical remission plus response rate after 14 weeks of 91.2% in UC and 78.5% in CD ( P = 0.02). Again, at 52 weeks the trend of the response in our study was favorable to CD patients despite a lack of statistical significance; in other real‐life studies, the two groups were comparable or there were higher response rates in UC .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The same results were shown by Kopylov et al with similar rates of response and remission both for CD and UC. Other authors found no difference in CD and UC cohorts after the induction phase, while in one study a higher clinical benefit in patients with UC was seen, with a cumulative clinical remission plus response rate after 14 weeks of 91.2% in UC and 78.5% in CD ( P = 0.02). Again, at 52 weeks the trend of the response in our study was favorable to CD patients despite a lack of statistical significance; in other real‐life studies, the two groups were comparable or there were higher response rates in UC .…”
Section: Discussionmentioning
confidence: 90%
“…Other authors found no difference in CD and UC cohorts after the induction phase, while in one study a higher clinical benefit in patients with UC was seen, with a cumulative clinical remission plus response rate after 14 weeks of 91.2% in UC and 78.5% in CD ( P = 0.02). Again, at 52 weeks the trend of the response in our study was favorable to CD patients despite a lack of statistical significance; in other real‐life studies, the two groups were comparable or there were higher response rates in UC . In addition, despite the better clinical results in CD, our endoscopic remissions at 52 weeks (15% UC and 27% CD) were very low compared with the other available data (41% of UC and 63% of CD in the VICTORY studies and 25.9% of CD and 47.8% of UC patients in a large Canadian cohort).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These data did not bear out in remaining real-world cohorts. For example, no differences were noted with any concomitant therapy in Israeli cohorts or the VICTORY or Cross Penine cohorts (3,(17)(18)(19). Regardless of these results, it is important to remember that the appeal of the relative safety for VDZ is decreased with combination therapy with corticosteroids and/or immunomodulators (20), and there also does not appear to be the same risk of immunogenicity or benefit of increased trough levels with concomitant immunomodulators for VDZ (21,22) (Table 2).…”
Section: Concomitant Immunosuppressive Therapymentioning
confidence: 99%
“…Almost half of the IBD patients respond to vedolizumab, but more than one-third of them relapse within 12-36 months from the induction phase [13][14][15][16][17][18][19][20][21][22][23]. These findings have boosted intensive research aimed at identifying predictors of response to the drug [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. It is now evident that prior exposure to anti-TNF α drugs associates with a reduced induction of clinical and endoscopic remission [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%